ANALISIS EFEKTIVITAS IKLAN TELEVISI KOPI INSTAN TOP COFFEE ENDORSER ”IWAN FALS” - Iwan Setyawan (Universitas muhammadiyah malang, 2014)
This study aims to measure the effectiveness of television advertising endorser Top Coffee